Immigration to Italy and return policies: a provocation, a wishful thinking or an opportunity? - Maria Luisa Gentileschi (Documents d'Anàlisi Geogràfica)
In Italy, the return of immigrants to their country of origin is practically absent in the media and in the debate among the operators or the general public. In the countries of arrival, immigrant labour, at first, alleviates pressure on the local labour market with a beneficial effect, but in time might also cause competition with local labour, impede renovation of production and keep the situation stationary. On the other hand, in the countries of origin, several authors have underlined the damage of massive population emigration of the young and skilled workforce and explored ways to encourage emigrants to come back with the intention of taking part in the development process.